2021
DOI: 10.48550/arxiv.2106.04345
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Intelligent Hybrid Model for Identity Document Classification

Nouna Khandan

Abstract: Digitization, i.e., the process of converting information into a digital format, may provide various opportunities (e.g., increase in productivity, disaster recovery, and environmentally friendly solutions) and challenges for businesses. In this context, one of the main challenges would be to accurately classify numerous scanned documents uploaded every day by customers as usual business processes. For example, processes in banking (e.g., applying for loans) or the Government Registry of BDM (Births, Deaths, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 83 publications
(119 reference statements)
0
4
0
Order By: Relevance
“…Once a matching model was found, a more intricate analysis was carried out to determine whether the matched model should be accepted or rejected. Khandan [10] proposed a method that combined SIFT and OCR for identity document classification. The study aimed to develop a method to classify identity documents with a confidence level for each match, which was determined by the number of matches in the SIFT model during each classification task.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Once a matching model was found, a more intricate analysis was carried out to determine whether the matched model should be accepted or rejected. Khandan [10] proposed a method that combined SIFT and OCR for identity document classification. The study aimed to develop a method to classify identity documents with a confidence level for each match, which was determined by the number of matches in the SIFT model during each classification task.…”
Section: Related Workmentioning
confidence: 99%
“…Some studies have also shown that incorporating visual features can enhance text-based document classification [22]. In the context of identity document classification, visual features often serve as the basis for classification methods [5,6], although some studies explore the combination of multiple types of information such as visual features and textual information [10], or visual features and spatial information [5,9]. CNN has been proposed as a classification method for all three categories examined in our study: general image classification [17], text document classification [19], and identity document classification [11].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations